Relationship between gestational weight gain and amount of postpartum bleeding - Runa Özelçi; Tuğba Kınay; İnci Kahyaoğlu; Özlem Moraloğlu Tekin; Berna Dilbaz (Journal of Contemporary Medicine, 2020)
AbstractBackground/Aims:To evaluate the effect of gestational weight gain on the amount of postpartum bleeding.Methods: An observational study reviewed medical records of with low-risk singleton pregnancies who delivered vaginally at 37 weeks of gestation or beyond between May 1 and November 1, 2018 at a tertiary referral center. Demographic and clinical characteristics were obtained from the medical records. The relationship between the increased rate in BMI during pregnancy and amount of blood loss in the postpartum first hour was evaluated. Results:A total of 411 women was included in the study. In the study population, the mean blood loss was 57.3±43.9 ml in the 3rd stage of labor and 113.2±76.9 ml in the postpartum first hour. No correlation was found between the increase in BMI during pregnancy and blood loss during the 3rd stage of labor (r=0.006) and postpartum first hour (r=0.037). Nulliparity, history of postpartum hemorrhage in previous pregnancy, premature rupture of membranes, and episiotomy were found to be risk factors for increased postpartum blood loss during the 1st hour (p lt; 0.05). Conclusions: Increase in BMI was not related with the amount of postpartum bleeding in women with low-risk pregnancy who had a vaginal delivery.